ANALYSIS OF ENVIRONMENTAL PROBLEMS IN TASIKMALAYA CITY: CHALLENGES AND ROLES OF STAKEHOLDERS - Ninis Dwi Rengganis; Kiki Endah (Proceeding of International Seminar on Agricultural Conservation and Cultural Heritage, 2025)
A clean environment plays an important role in human survival, especially for health because in essence every citizen has the right to live in a healthy environment, so in this case the government and society have an obligation to provide environmental comfort for the community. However, in fact, environmental problems are still a major challenge in Indonesia. Tasikmalaya City is one of the cities facing environmental problems. The significant population growth and the lack of government focus on these problems are some of the reasons why these problems are still ongoing today. Thus, this is the main focus of the study with the aim of analyzing the role of the government and society in dealing with environmental problems in Tasikmalaya City. The research method used is a descriptive method with the data collection technique used is a literature study produced from secondary data in the form of websites, books, journals, news and other literature relevant to this research. Based on this research, the author analyzes that: 1) The Tasikmalaya City Government does not prioritize waste problems 2) There is a shift in land use in Tasikmalaya City 3) Lack of education to the community regarding the importance of the environment.